In vivo pulse-echo measurement of apparent broadband attenuation and Q factor in cortical bone: a preliminary study. (19th July 2021) - Minonzio, Jean-Gabriel; Han, Chao; Cassereau, Didier; Grimal, Quentin
Abstract: Quantitative ultrasound (QUS) methods have been introduced to assess cortical bone health at the radius and tibia through the assessment of cortical thickness (Ct.Th), cortical porosity and bulk wave velocities. Ultrasonic attenuation is another QUS parameter which is not currently used. We assessed the feasibility of in vivo measurement of ultrasonic attenuation in cortical bone with a broadband transducer with 3.5 MHz center frequency. Echoes from the periosteal and endosteal interfaces were fitted with Gaussian pulses using sparse signal processing. Then, the slope of the broadband ultrasonic attenuation (Ct.nBUA) in cortical bone and quality factor Q 11 − 1 were calculated with a parametric approach based on the center-frequency shift. Five human subjects were measured at the one-third distal radius with pulse-echo ultrasound, and reference data was obtained with high-resolution x-ray peripheral computed tomography (Ct.Th and cortical volumetric bone mineral density (Ct.vBMD)). Ct.Th was used in the calculation of Ct.nBUA while Q 11 − 1 is obtained solely from ultrasound data. The values of Ct.nBUA (6.7 ± 2.2 dB MHz −1 .cm −1 ) and Q 11 − 1 (8.6 ± 3.1%) were consistent with the literature data and were correlated to Ct.vBMD ( R 2 = 0.92, p < 0.01, RMSE = 0.56 dB.MHz −1 .cm −1, and R 2 = 0.93, p < 0.01, RMSE = 0.76%). This preliminary study suggests that the attenuation of an ultrasound signal propagating in cortical bone can be measured in vivo at the one-third distal radius and that it provides an information on bone quality as attenuation values were correlated to Ct.vBMD. It remains to ascertain that Ct.nBUA and Q 11 − 1 measured here exactly reflect the true (intrinsic) ultrasonic attenuation in cortical bone. Measurement of attenuation may be considered useful for assessing bone health combined with the measurement of Ct.Th, porosity and bulk wave velocities in multimodal cortical bone QUS methods.